Verbal Indicators of Personal Identity in The Road Past Altamont by Gabrielle Roy - Kuzikova, Svitlana; Vertel , Anton; Zlyvkov, Valeriy; Lukomska, Svitlana (East European Journal of Psycholinguistics, 2021)
The present paper explores personal identity linguistic indicators detected in The Road Past Altamont by Gabrielle Roy. Works by this Canadian writer, public personality, and significant figure in French Canadian literature are of interest to a broad audience today in Canada, where almost all her books have been translated into English, and abroad. Written in a fluid, spare style, they are distinguished by lively narration and a keen sense of observation. Her literature approaches the world and people with clear sight and compassion. The Road Past Altamont (1966) by Roy is one of the most original in Canada, as varied as it is cohesive. The novel is dedicated to the coverage of the autobiographical narrative, the peculiarities of the personal identity crisis for different age groups, the succession of generations. These existential problems are actualized in crisis life situations. Despite containing four independent texts, The Road Past Altamont, each of which tells a finished story, is not a collection of short stories but a novel-saga. Its genre is both fragmented and unified, and it has a flexible structure based on the concept of the human life course. The four stories in this novel are connected not only by the main character at different points in her life but also by the themes that explore the changes, ageing, and society’s relation to the elders. The study aims to single out verbal indicators of personal identity obtained from the second part, “The old man and the child” of the Roy’s novel and the music album of the same name, created on its basis in 2021. Among the main findings are the defining psycholinguistic markers of time and space in the discourse of “The old man and the child” that encompass personal identity cognitive component. Hence, it is possible to treat the transformation of identity in the modern world in terms of constructing “self” as a reflexive project - implementing an integral, biographical story being changed in a polyvariant context of choice.